Isolation Of Potentially Pathogenic Escherichia Coli O157:H7 From The Water Sources - M.THENMOZHI, (International Journal of Pharma and Bio Sciences, 2010)
Water a universal solvent and a basic requirement for all, if becomes prone to contaminants and unfit for use, would cause hazardous health effects on humans and animals. Most of the diseases outbreaks are reported due to exposure to contaminated water. Both solid waste and chemical mixture prove contaminant to water. Many drinking water and recreational water sources are reported nowadays with contamination of a particular strain of E.coli known as E.coli 0157:H7. Cattle or humans with 0157:H7 infection can contaminate steams, lakes, irrigation ditches or swimming pools with feaces. We conducted a preliminary study to know the frequency of this pathogenic strain and studied characteristics in drinking water sources, collected from different areas in Namakkal district.